2008
DOI: 10.1029/2007jd009065
|View full text |Cite
|
Sign up to set email alerts
|

A system for operational aerosol optical depth data assimilation over global oceans

Abstract: [1] In this study, we present an aerosol data assimilation system destined for operational use at the Fleet Numerical Meteorological and Oceanographic Center (FNMOC). The system is an aerosol physics version of the Naval Research Laboratory (NRL) Atmospheric Variational Data Assimilation System (NAVDAS) that is already operational. The purpose of this new system, NAVDAS-Aerosol Optical Depth (NAVDAS-AOD) is to improve the NRL Aerosol Analysis and Prediction System (NAAPS)'s forecasting capability by assimilati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
247
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 251 publications
(263 citation statements)
references
References 54 publications
5
247
0
Order By: Relevance
“…In particular, studies have shown notable improvements in aerosol forecasting through the assimilation of satellite aerosol products, mostly from daytime observations (e.g., Zhang et al, 2008aZhang et al, , 2011Zhang et al, , 2014Yumimoto et al, 2008;Uno et al, 2008;Benedetti et al, 2009;Schutgens et al, 2010;Sekiyama et al, 2010). To capture the diurnal cycle, the aerosol modeling community requires nighttime satellite aerosol data hav-ing broad spatial coverage and high temporal resolution to further advance aerosol, visibility, and air quality forecasts (e.g., Zhang et al, 2011Zhang et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, studies have shown notable improvements in aerosol forecasting through the assimilation of satellite aerosol products, mostly from daytime observations (e.g., Zhang et al, 2008aZhang et al, , 2011Zhang et al, , 2014Yumimoto et al, 2008;Uno et al, 2008;Benedetti et al, 2009;Schutgens et al, 2010;Sekiyama et al, 2010). To capture the diurnal cycle, the aerosol modeling community requires nighttime satellite aerosol data hav-ing broad spatial coverage and high temporal resolution to further advance aerosol, visibility, and air quality forecasts (e.g., Zhang et al, 2011Zhang et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Many successful applications of these data to global-and regional-scale questions are already presented in the literature. They range from assessing zonal mean or global aerosol short-wave forcing [37][38][39][40][41][42] and regional long-wave forcing [43], to improving aerosol forecasting through data assimilation [44,45], monitoring dust and pollution plume evolution [46,47] and air quality [48,49], mapping aerosol air mass type evolution [50], and validating aerosol transport model AOD simulations [51,52]. In each case, ways of exploiting the strengths of the MISR and MODIS data have been found, and in many cases, independent validation was performed specific to the application.…”
Section: Application Of Misr and Modis Aerosol Productsmentioning
confidence: 99%
“…Although the median wind speed of the ESOA region is under 10 m s −1 , the wind speeds can exceed 12 m s −1 in more than 10 % of cases. Thus, the subsurface ocean bubble effects may need to be considered for applications that use instantaneous MODIS DT retrievals, such as operational aerosol data assimilation (Zhang et al, 2008(Zhang et al, , 2014.…”
Section: Applying Ocean Bubble Correction To the Esoamentioning
confidence: 99%
“…Given that sea salt aerosol production, specular reflection (sun glint), and whitecapping all covary with wind speed, AOD retrievals are a potentially confounded system. Some Level 3 products (e.g., Zhang and Reid, 2008;Shi et al, 2011a) include an empirical correction for wind-speedrelated bias to retrieved AOD. Some Level 2 satellite retrievals (e.g., Sayer et al, 2010Sayer et al, , 2012Jackson et al, 2013;Levy et al, 2013;Limbacher and Kahn, 2014) also incorporate wind speed data into the radiative transfer calculations using parameterizations of wind effects on whitecaps and bubble rafts.…”
Section: Introductionmentioning
confidence: 99%